Comparative Analysis of the use of Band Heaters and Infrared Heaters to Save Energy on Injection Molding Machines Type Borche Bi 320T - Khairin Amalia Cholis; Vinan Viyus (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to compare the energy efficiency between the use of a heater band and an infrared heater on an injection molding machine type borche bi 320T. The injection molding machine is one of the main pieces of equipment in the manufacturing process of plastic products and plays an important role in shaping various consumer and industrial products. One of the critical aspects of the operation of injection molding machines is the significant energy consumption, especially related to heating. This study was conducted by measuring the energy consumption of both types of heaters under the same operational conditions. The results showed that the energy consumption of using a band heater was 46.9 kW, while the infrared heater was 38.9 kW, significantly more energy efficient by 17.1% compared to the band heater. Although the initial installation cost of the infrared heater is 87% higher than that of the band heater, the energy savings generated from the infrared heater can reduce operating costs by approximately 39 million per year. Higher energy efficiency means lower electricity costs and, thus, more efficient total production costs. The use of infrared heaters also has a positive impact on the environment. Reduced energy consumption means reduced greenhouse gas emissions from power generation. Therefore, besides the economic benefits, the use of infrared heaters is also in line with sustainability and environmentally friendly practices.